Sentiment Analysis of Tribal, Religion, and Race with LIWC - Utomo, Prasetyo Adi; Karyawati, AAIN Eka (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2021)
During this pandemic, social media has become a major need as a means of communication. One of the social media used is Twitter by using messages referred to as tweets. In Indonesia itself, there are various tribes, religions, and races in their society so the use of these names is also become commonly used. However, sometimes, the use of the name is followed by negative sentiment that used to insult and aimed at an individual or group. To filter that kind of tweets, a sentiment analysis was performed with LIWC method that divides tweets into 3 classes of positive, neutral, and negative. From the sentiment analysis that has been performed, the average score for precision is 69.62%, recall is 70%, and f-measure is 69.81%